1991
DOI: 10.1128/jb.173.19.6289-6293.1991
|View full text |Cite
|
Sign up to set email alerts
|

Transposon mutagenesis in Proteus mirabilis

Abstract: A technique of transposon mutagenesis involving the use of TnS on a suicide plasmid was developed for Proteus mirabilis. Analysis of the resulting exconjugants indicated that TnS transposed in P. mirabilis at a frequency of ca. 4.5 x 10-6 per recipient cell. The resulting mutants were stable and retained the transposon-encoded antibiotic resistance when incubated for several generations under nonselective conditions. The frequency of auxotrophic mutants in the population, as well as DNA-DNA hybridization to tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
114
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(115 citation statements)
references
References 13 publications
1
114
0
Order By: Relevance
“…BB2000 grown on agar was used as a control and typically showed >80% swarmer cells at 40-,um average length under inducing conditions. As shown in Table 2, Elo-mutants accounted for 10% (7 (Fig. 2C).…”
Section: Resultsmentioning
confidence: 99%
“…BB2000 grown on agar was used as a control and typically showed >80% swarmer cells at 40-,um average length under inducing conditions. As shown in Table 2, Elo-mutants accounted for 10% (7 (Fig. 2C).…”
Section: Resultsmentioning
confidence: 99%
“…These strains have been labelled PRM1 through PRM84. PRM1 is the parental strain of the mutants described by Belas and colleagues (4,5). After introduction of antibiotic resistance plasmids into PRM1 and PRM2, we found that about half of the transconjugants displayed new colony phenotypes characterized by narrower terraces.…”
Section: Methodsmentioning
confidence: 99%
“…Others have begun to demonstrate the genetic potential of using P. mirabilis as a morphogenetic model system (1,4,5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmid pRS110 was digested with SacI and KpnI, and a 2n5 kb fragment containing luxSh ::aphA ::hluxS was ligated to pGP704 (Miller & Mekalanos, 1988) also digested with SacI and KpnI, resulting in pRS112. This plasmid was transformed into E. coli SM10 λpir and conjugally transferred to P. mirabilis BB2000 by filter mating (Belas et al, 1991a). Mutation of the chromosomal copy of luxS PM was confirmed by antibiotic resistance spectrum (Km R Ap S ), PCR amplification of luxS PM locus from the putative luxS strain, and measurement of AI-2 activity using the V. harveyi luminescence assay.…”
Section: Methodsmentioning
confidence: 99%